A SUCCESSFULL PNEUMATIC RETINOPEXY FOR THE TREATMENT OF RHEGMATOGENOUS RETINAL DETACHMENT FOLLOWING BLUNT TRAUMA - Wahyudi, I Nyoman Surya Ari; Metita, Mirza (Indonesian Vitreoretinal Society, 2024)
Introduction: To report the successful single operative method using Pneumatic Retinopexy as management of rhegmatogenous retinal detachment following ocular blunt trauma. Case Report: A 17 years old boy admitted to clinic with blurred vision in lower part of right eye that worsen over time for 3 weeks with a history of blunt trauma. Initial examination showed the visual acuity of 6/6 on both eyes. Posterior segment evaluation revealed superior retinal detachment on right eye with macular sparing. The main retinal break located in superotemporal part. Patient then treated with Pneumatic Retinopexy using SF6 gas followed by a serial of laser demarcation on right eye. Three months follow up after procedure resulted in reattachment of retina with preserved visual acuity of 6/6 and reduced visual field defect on right eye. Discussion: Rhegmatogenous retinal detachment is the most common form of retinal detachment. Specific procedure of Pneumatic Retinopexy may vary based on expert preference respective surgery. However procedures should always include retinopexy, tamponade by gas and posturing of the patient. Conclusion: Pneumatic Retinopexy is a minimally invasive procedure that can be performed for the management of rhegmatogenous retinal detachment. In order to optimizing post operative outcome, ophthalmologists must be able to select suitable patient, proper examinations and good surgical techniques to achieve a high success rate.